Antiretroviral therapy as a factor protective against anal dysplasia in HIV-infected males who have sex with males. - Carmen Hidalgo-Tenorio; Mar Rivero-Rodriguez; Concepción Gil-Anguita; Mercedes Lopez De Hierro; Pablo Palma; Jessica Ramírez-Taboada; Javier Esquivias; Miguel Angel López-Ruz; Rosario Javier-Martínez; Juan Pasquau-Liaño (PLoS ONE)
Objectives Chronic infection with oncogenic HPV genotype is associated with the development of anal dysplasia. Antiretroviral therapy (ART) has been shown to decrease the incidence of cervical carcinoma in women with HIV. We sought to: 1) describe the prevalence and grade of anal dysplasia and HPV infection in our study subjects; 2) analyze the grade of correlation between anal cytology, PCR of high-risk HPV, and histology; 3) identify the factors associated with the appearance of ≥ AIN2 lesions. Design Cross-sectional, prospective study. Methods A cohort of HIV-positive males (n = 140, mean age  = 37 years) who have sex with males (MSM) had epidemiological, clinical and analytical data collected. Anal mucosa samples were taken for cytology, HPV PCR genotyping, and anoscopy for histological analysis. Results Within the cohort, 77.1% were being treated with ART, 8.5% anoscopy findings were AIN2, and 11.4% carcinoma in situ; 74.2% had high-risk (HR), 59.7% low-risk (LR) HPV genotypes and 46.8% had both. The combination of cytology with PCR identifying HR-HPV better predicts the histology findings than either of these factors alone. Logistic regression highlighted ART as a protective factor against ≥ AIN2 lesions (OR: 0.214; 95%CI: 0.054-0.84). Anal/genital condylomas (OR: 4.26; 95%CI: 1.27-14.3), and HPV68 genotype (OR: 10.6; 95%CI: 1.23-91.47) were identified as risk factors. Conclusions In our cohort, ART has a protective effect against dysplastic anal lesions. Anal/genital warts and HPV68 genotype are predictors of ≥ AIN2 lesions. Introducing PCR HPV genotype evaluation improves screening success over that of cytology alone.